Line side placement for shorter assembly line worker paths. (1st February 2020) - Sedding, Helmut A.
Abstract: Placing material containers at moving assembly lines is an intriguing problem because each container position influences worker paths. This optimization is relevant in practice as worker walking time accounts for about 10–15% of total work time. Nonetheless, we find few computational approaches in the literature. We address this gap and model walking time to containers, then optimize their placement. Our findings suggest this reduces walking time of intuitive solutions by an average of 20%, with considerable estimated savings. To investigate the subject, we formulate a quintessential optimization model for basic sequential container placement along the line side. However, even this core problem turns out as strongly NP-complete. Nonetheless, it possesses several polynomial cases that allow to construct a lower bound on the walking time. Moreover, we discover exact and heuristic dominance conditions between partial placements. This facilitates an exact and a truncated branch-and-bound solution algorithm. In extensive tests, they consistently deliver superior performance compared to several mixed integer programming and metaheuristic approaches. To aid practitioners in quickly recognizing instances with high optimization potential even before performing a full optimization, we provide a criterion to estimate it with just few measurements.